2006
DOI: 10.2475/10.2006.02
|View full text |Cite
|
Sign up to set email alerts
|

Ordovician 40Ar/39Ar phengite ages from the blueschist-facies Ondor Sum subduction-accretion complex (Inner Mongolia) and implications for the early Paleozoic history of continental blocks in China and adjacent areas

Abstract: We obtained 453.2 ± 1.8 Ma and 449.4 ± 1.8 Ma (2{sigma}) laser step-heating 40Ar/39Ar plateau ages for phengite from quartzite mylonites from the blueschist-facies Ondor Sum subduction-accretion complex in Inner Mongolia (northern China). These ages are within error of the inverse isochron ages calculated using the plateau steps and the weighted mean ages of total fusion of single grains. The compositional change from glaucophane in the cores to crossite in the rims of blue amphiboles, as revealed by electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(83 citation statements)
references
References 166 publications
2
77
0
Order By: Relevance
“…They yield sensitive high-resolution ion microprobe (SHRIMP) zircon ages of 1973 + 4 Ma and 1834 + 5 Ma, with a core residual age of 2.0-2.1 Ga (Peng et al 2005(Peng et al , 2007. Zhao et al (2001aZhao et al ( , b, 2005Zhao et al ( , 2006, Wilde et al (2003), and Kröner et al (2005a, b, 2006 have suggested that the c. 1.9-1.8 Ga granulite event in the NCC is related to the continent-continent collision between the Eastern and Western Blocks of the craton. This model is supported by the interpretation of clockwise metamorphic P-T -t paths that show crustal thickening related metamorphism at 1.85 Ga, in support of a collision at this time.…”
Section: High-pressure Granulitesmentioning
confidence: 99%
“…They yield sensitive high-resolution ion microprobe (SHRIMP) zircon ages of 1973 + 4 Ma and 1834 + 5 Ma, with a core residual age of 2.0-2.1 Ga (Peng et al 2005(Peng et al , 2007. Zhao et al (2001aZhao et al ( , b, 2005Zhao et al ( , 2006, Wilde et al (2003), and Kröner et al (2005a, b, 2006 have suggested that the c. 1.9-1.8 Ga granulite event in the NCC is related to the continent-continent collision between the Eastern and Western Blocks of the craton. This model is supported by the interpretation of clockwise metamorphic P-T -t paths that show crustal thickening related metamorphism at 1.85 Ga, in support of a collision at this time.…”
Section: High-pressure Granulitesmentioning
confidence: 99%
“…These observations imply that the Solonker suture zone continued to the coastal area of the Sea of Japan (Figs. 1, 2;de Jong et al 2006). The South Kitakami terrane of northeast Japan (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors explored the possibility that the Central Asian Orogenic Belt continues southeastward from mainland Asia into the 250-235 Ma-old, mainly metasedimentary Hida-Oki terrane in Japan ( Fig. 1; Arakawa et al 2000;Jahn et al 2000;de Jong et al 2006). Indeed, metamorphic rocks and synorogenic granites from the easternmost Central Asian Orogenic Belt in northeastern China yielded ca.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous study, four periods of metamorphism can be identified in the central Inner Mongolia since the Paleozoic (Figure): the first period is the high P/T metamorphism occurred in the Late Silurian (426 Ma), represented by the Early Paleozoic Ondor Sum Group which is attributed to the subduction of the Paleo-Asian ocean [De et al, 2006]; the second period is the medium P/T metamorphism in the early Devonian (400 Ma), represented by the Baoyintu Group in the western Inner Mongolia, which is related to the orogenic progress as a result of collision, following the closure of the Paleo-Asian ocean [Chen et al, 2015]; the third period is the low P/T metamorphism in the Middle-Late Carboniferous (309-345 Ma), represented by Xilin Gol complex, which is probably related to the regional extension after collision process; the fourth period is the low-medium P/T metamorphism in the Early Triassic (240 Ma), represented by the regional greenschist to epidote-amphibolite facies metamorphism in the central Inner Mongolia, which is attributed to the thickening process due to the closure of limited ocean basins. It is suggested that the Solonker suture zone may not represent a typical suture after closure of the Paleo-Asian ocean but a tectonic belt that records the closure of the limited basins in the early Mesozoic.…”
Section: P a L E O G E O D Y N A M I C Smentioning
confidence: 99%